Pengaruh Keberlanjutan (Sustainability), Trend Fashion Dan Komunitas Digital Terhadap Keputusan Pembelian Pakaian Thrift Di Kecamatan Lowokwaru - Sholahudin, Dimas; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of sustainability (X1), fashion trends (X2), and digital thrifting communities (X3) on purchasing decisions (Y) of thrift clothing in Lowokwaru District. The background of the research is based on the increasing phenomenon of thrifting, which is not only perceived as an affordable shopping alternative but also as a lifestyle associated with environmental issues and digital development. This research employed a quantitative approach by distributing questionnaires to 105 respondents selected based on specific criteria. Data analysis was conducted through validity, reliability, normality tests, and multiple linear regression using SPSS. The results indicate that sustainability has a significant effect on purchasing decisions, while fashion trends and digital thrifting communities do not show a significant effect. Theoretically, this reflects a knowledge–behavior gap among consumers, where knowledge about trends or digital engagement does not directly influence purchasing decisions. Practically, this study suggests that thrift marketing strategies in Lowokwaru should focus more on emphasizing the sustainability value of products. Keywords: Sustainability, Fashion Trends, Digital Thrifting Communities, Purchasing Decisions, Thrift